COMMUNITY EMPOWERMENT IN BUILDING SUSTAINABLE AND DIGNIFIED COMMUNITY EDUCATION - Faliza, Nur; Asfahani, Asfahani; Fahrizal, Effan (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
The importance of community education is increasingly recognized as essential for fostering social cohesion, lifelong learning, and sustainable development, especially in marginalized communities. However, many existing initiatives fail to achieve long-term sustainability and do not adequately respect the cultural dignity of the communities they serve. This community empowerment project aimed to develop a sustainable and dignified community education model that is deeply rooted in the cultural and social contexts of the community. The project employed a Participatory Action Research (PAR) method, involving community members as co-researchers in identifying educational needs, developing strategies, and implementing solutions. The collaborative approach ensured that the educational programs were culturally relevant, addressing the specific challenges and aspirations of the community in Lhokseumawe. Local educational committees were established, and community members were trained in leadership roles to ensure the sustainability of the initiative. The results demonstrated significant improvements in community engagement, educational outcomes, and social cohesion. Community members took active roles in the educational process, resulting in a stronger sense of ownership and responsibility. The integration of cultural heritage into the curriculum enhanced the relevance and effectiveness of education, while the establishment of sustainable structures ensured the long-term impact of the project. The findings underscore the importance of participatory, culturally responsive approaches in building sustainable and dignified community education systems. In conclusion, this project provides a successful model for future initiatives, highlighting the need for continued community involvement, cultural relevance, and sustainability in educational development efforts.